The influence of NWOM in the consumers’ decision-making process in the Tourism industry - Melo, Inês Patrícia Gomes de (2018)
Online feedback tools, such as electronic Word-of-Mouth (eWOM), have been widely used to share knowledge and information online between consumers about products or services, having become an important tool for consumers and being considered a reliable source. Based on relevant theories and previous works, it has been proved that Negative Word-of-Mouth (NWOM) has been influencing significantly consumers’ decision-making process, especially regarding the Tourism industry and that this sector is the most strongly influenced by eWOM. To investigate the impact of NWOM on consumers in the industry of Tourism, an online survey was created. Different negative hotel reviews were presented to 249 individuals. Quantitative data was generated to investigate the impact of these reviews on consumers’ brand attitude, purchase intentions and NWOM intentions, in two distinct stages of the travel planning process, namely the search phase vs the post-purchase phase, when a new purchase was being planned. The conclusions supported the existence of a significant impact of NWOM on users that are exposed to negative reviews in the Tourism sector. Furthermore, users in the post-purchase phase were less susceptible to NWOM than those in the search phase, which means that NWOM communication mostly affects consumers who are in the search phase of the travel planning process. This study contributes to companies, especially hotels, by identifying useful research that can help them understanding the power of negative information on consumers, taking advantage of online consumer reviews as a new marketing tool. Finally, limitations are discussed and future research is proposed.